Original article Density and spatial pattern of β-amyloid (Aβ) deposits in corticobasal degeneration - A. Armstrong, Richard (Folia Neuropathologica, 2011)
Corticobasal degeneration (CBD) is a rare, progressive movement disorder characterized neuropathologically by widespread neuronal and glial pathology including tau-immunoreactive neuronal cytoplasmic inclusions (NCI), oligodendroglial inclusions (GI), and astrocytic plaques (AP). However, β -amyloid (A β) deposits have been observed in the cerebral cortex and/or hippocampus in some cases of CBD. To clarify the role of Aβ deposition in CBD, the densities and spatial patterns of the Aβ deposits were studied in three cases. In two cases, expressing apolipoprotein E (APOE) genotypes 2/3 or 3/3, the densities of the Aβ deposits were similar to those in normal elderly brain. In the remaining case, expressing APOE genotype 3/4, Aβ deposition was observed throughout the cerebral cortex, sectors CA1 and CA2 of the hippocampus, and the molecular layer of the dentate gyrus. The densities of the Aβ deposits in this case were typical of those observed in Alzheimer’s disease (AD). In the three cases, clustering of Aβ deposits, with clusters ranging in size from 200 to >6400 µm in diameter, was evident in 25/27 (93%) of analyses. In addition, the clusters of Aβ deposits were regularly distributed parallel to the tissue boundary in 52% of analyses, a spatial pattern similar to that observed in AD. These results suggest: (1) in some CBD cases, Aβ pathology is age-related, (2) more extensive Aβ deposition is observed in some cases, the density and spatial patterns of the Aβ deposits being similar to AD, and (3) extensive deposition of Aβ in CBD may be associated with APOE allele e4.